Impact of intrauterine exposure to betamethasone on the testes and epididymides of prepubertal rats - de Barros, Jorge Willian Franco [UNESP]; Borges, Cibele dos Santos [UNESP]; Missassi, Gabriela [UNESP]; Pacheco, Tainá Louise [UNESP]; De Grava Kempinas, Wilma [UNESP] (Elsevier, 2018)
Therapy with betamethasone, a synthetic glucocorticoid, is used in cases of preterm birth risk, in order to promote fetal lung maturation, and decrease neonatal mortality and morbidity. However, late reproductive disorders related to the prenatal exposure to this compound have been reported by our Laboratory, in both male and female rats. Thus, the present study aimed to evaluate the impact of betamethasone on postnatal reproductive development, during pre-puberty, of male offspring exposed in utero to this synthetic glucocorticoid. For this purpose, pregnant Wistar rats were allocated into two groups: Control, treated with saline, and the group treated with betamethasone at 0.1 mg/kg/day. Control and betamethasone groups were treated with intramuscular injection on gestational days 12, 13, 18 and 19, critical days of prenatal reproductive development. The treatment is associated with reduced body and organ weights, disorders in initial reproductive parameters of pre-pubertal male offspring exposed in utero to betamethasone, such as reduction of anogenital distance, alterations in histomorphometric parameters and immunostaining pattern of androgen and estrogen receptors on testicles and epididymides. Our results suggest that prenatal exposure to betamethasone potentially causes reproductive reprogramming and impairs male postnatal reproductive development. This data raise concerns about the use of betamethasone for human antenatal therapy.
Keywords: Betamethasone; Male reproductive development; Pre-puberty; Rats